Test slice difference technique for low-transition test data compression. - Rau, Jiann-Chyi (Journal of Applied Science and Engineering)
This paper presents a low power strategy for test data compression and a new decompression scheme for test vectors. In our method, we propose an efficient algorithm for scan chain reordering to deal with the power dissipation problem. Further, we also propose a test slice difference (TSD) technique to improve test data compression. It is an efficient method and only needs one extra scan cell. In experimental results, the scheme that we presented achieve high compression ratio. The power consumption is also better compared with other well-known compression techniques.